Electron microscope weak-beam imaging of stacking fault tetrahedra: observations and simulations - Jenkins, M; Zhou, Z; Dudarev, S; Sutton, A; Kirk, M (2006)
Weak-beam diffraction-contrast electron microscope images of stacking-fault tetrahedra (SFT) have been simulated by solving numerically the Howie-Basinski equations, which are well suited for studying the dependence of image contrast on experimental parameters. These simulated images are in good qualitative agreement with experimental transmission electron micrographs. The visibility of small SFT and the relationship between measured image sizes and real SFT sizes are discussed.